Libraries and the global retreat of democracy : confronting polarization, misinformation, and suppression - Taylor, Natalie Greene; Kettnich, Karen; Gorham, Ursula; Jaeger, Paul T. (Advances in librarianship ;, 2021)
This latest volume of the Advances in Librarianship series presents original research exploring the modern state of democracies and social institutions, the contributions of libraries to the health and progress of democracies, and the political problems currently facing libraries as institutions. It details the best practices of library programs that provide political literacy education and promote civic engagement within communities. These practices include ways in which libraries can help diffuse political polarization, address significant policy issues of our day, promote political information literacy, support civic engagement, and facilitate participation in democratic processes. Libraries and the Global Retreat of Democracy: Confronting Polarization, Misinformation, and Suppression is structured in three sections - questions of personal and state democracy, investigations of how the information infrastructure shapes these democracies, and explorations of the ways that libraries can and do contribute to democracy. Situating libraries within political conversations, highlighting their centrality to these discussions, Libraries and the Global Retreat of Democracy focuses on how libraries coordinate their work in political and information literacy and how these efforts can be improved, he recommendations and examples within which will serve as inspiration and motivation to its readers.